PENGARUH AKUNTANSI PERTANGGUNGJAWABAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA HOTEL TRANSIT SYARIAH MEDAN - Aisyah, siti; Rahmalia, Dwi (JURNAL AKUNTANSI DAN INVESTASI, 2020)
This research was conducted with the aim of looking at the effect of accountability accounting and organizational commitment on the employee performance of the Hotel Transit Syariah Medan. The population in this study amounted to 32 people consisting of all employees of the Hotel Transit Syariah Medan. The sampling technique of this research is saturated sample.The data collection technique in this research was carried out using a questionnaire distributed to respondents. The analysis technique used in this study is multiple linear regression analysis techniques. The results of the analysis obtained from this study show that the results of the t test for variable X1 show that responsibility accounting has an effect on employee performance, and for X2, it is found that organizational commitment has no effect on employee performance. For the F test, the results show that the responsibility accounting variables and organizational commitment simultaneously affect the performance of the employees of the Hotel Transit syariah Medan. The amount of the Adjusted R Square coefficient of determination obtained is 96.6%,